OP0076 Isotemporal substitution of sedentary time with physical activity in fibromyalgia: association with quality of life and disease impact. the al-Ándalus project. (12th June 2018) - Gavilán-Carrera, B.; Mekary, R.A.; Borges-Cosic, M.; Acosta-Manzano, P.; Álvarez-Gallardo, I.C.; Segura-Jiménez, V.
Abstract : Background: There is an awareness of detrimental health effects of sedentary time (ST) in fibromyalgia. 1 2 However, data are limited on how replacing ST with physical activities of different intensities may be related to the typically reduced quality of life of these patients. Increasing time in one behaviour requires decreasing time in another but classic regression models are not able to directly target these substitutions. Hence, the isotemporal substitution paradigm (a novel model to study the estimated effects of one activity for another 3 ), might allow us to better understand the relationship between ST, physical activity and perceived health status in fibromyalgia. Objectives: To investigate the association of replacing ST with light physical activity (LPA) or moderate-to-vigorous physical activity (MVPA) with quality of life and disease impact in women with fibromyalgia. Methods: In total, 407 women with fibromyalgia (51.4±7.6 years old) were included in this cross-sectional study. The time spent in ST and PA intensity levels was objectively measured with triaxial accelerometry. Quality of life and disease impact were assessed using the 36-item Short-Form Health Survey (SF-36) and the Revised Fibromyalgia Impact Questionnaire (FIQR), respectively. An isotemporal substitution approach was used to estimate the associations between the substitution of 30 min of ST with an equivalent time of LPA or MVPA and the outcomes. Analyses were controlled for age, current occupational status, fat percentage, and antidepressant consumption. Results: Substituting 30 min of ST with LPA in the isotemporal model was associated with better bodily pain ( B =0.55), vitality ( B =0.74) and social functioning ( B =1.45) of SF-36 and better scores at all of the domains of FIQR (function, overall impact, symptoms severity, and total impact) ( B ranging from −0.95 to −0.27), all p<0.05. When 30 min of ST were replaced with MVPA, significantly better physical role ( B =2.30) and social functioning ( B =4.11) of the SF-36 and function of FIQR ( B =-0.73) were observed (all p<0.05). Conclusions: Allocating time of sedentary behaviour to either LPA or MVPA was generally associated with better quality of life and lower disease impact in women with fibromyalgia. The isotemporal models suggest that LPA may be beneficial for a larger number of domains, while MVPA may establish greater changes in the outcomes. These results reinforce the importance of moving towards less sedentary lifestyle in fibromyalgia, although these findings should be investigated in longitudinal, experimental research. References: [1] Ellingson LD, et al. J Pain2012Feb;13(2):195–206. [2] Segura-Jiménez V, et al. Scand J Med Sci 2017Jan;27(1):83–92. [3] Mekary RA, et al. Am J Epidemiol2009May;170(4):519–27. Acknowledgements: This study was supported by the Spanish Ministries of Economy and Competitiviness (I+D+ i DEP2010–15639; I+D+I DEP2013–40908 R, BES-2011–047133; BES-2014–067612) and the Spanish Ministry of Education (FPU14/02518; FPU15/00002) Disclosure of Interest: None declared